Elementary technical mathematics - Ewen, Dale, 1941- (Boston, MA : Cengage Learning, 2019)
Elementary Technical Mathematics, 12th Edition, helps students with minimal math backgrounds successfully prepare for technical, trade, allied health, or tech prep programs. Author Dale Ewen focuses on fundamental concepts in basic arithmetic: the metric system and measurement, algebra, geometry, trigonometry, and statistics. Thousands of examples, exercises, and applications cover such fields as industrial and construction trades, electronics, agriculture/horticulture, allied health, CAD/drafting, HVAC, welding, auto/diesel service, aviation, natural resources, culinary arts, and business/personal finance$1 (Bto engage students and provide them with the math background they need to succeed in future courses and careers.s
Chapter 1: Basic Concepts -- 1.1: Review of Basic Operations (40) -- 1.2: Order of Operations (13) -- 1.3: Area and Volume (29) -- 1.4: Formulas (13) -- 1.5: Prime Factorization (18) -- 1.6: Introduction to Fractions (11) -- 1.7: Addition and Subtraction of Fractions (34) -- 1.8: Multiplication and Division of Fractions (30) -- 1.9: The U.S. System of Weights and Measures (37) -- 1.10: Addition and Subtraction of Decimal Fractions (31) -- 1.11: Rounding Numbers (9) -- 1.12: Multiplication and Division of Decimal Fractions (22) -- 1.13: Percent (9) -- 1.14: Rate, Base, and Part (17) -- 1.15: Powers and Roots (6) -- 1.16: Applications Involving Percent: Business and Personal Finance (8) -- 1: Review -- 1: Test -- Chapter 2: Signed Numbers and Powers of 10 -- 2.1: Addition of Signed Numbers (13) -- 2.2: Subtraction of Signed Numbers (14) -- 2.3: Multiplication and Division of Signed Numbers (19) -- 2.4: Signed Fractions (18) -- 2.5: Powers of 10 (15) -- 2.6: Scientific Notation (24) -- 2.7: Engineering Notation (12) -- 2: Review -- 2: Test -- 2: Cumulative Review -- Chapter 3: The Metric System -- 3.1: Introduction to the Metric System (29) -- 3.2: Length (30) -- 3.3: Mass and Weight (30) -- 3.4: Volume and Area (20) -- 3.5: Time, Current, and Other Units (20) -- 3.6: Temperature (15) -- 3.7: Metric and U.S. Conversion (38) -- 3: Review -- 3: Test -- Chapter 4: Measurement -- 4.1: Approximate Numbers and Accuracy (22) -- 4.2: Precision and Greatest Possible Error (22) -- 4.3A: The Vernier Caliper (2) -- 4.3B: The Vernier Caliper (1) -- 4.4A: The Micrometer Caliper (9) -- 4.4B: The Micrometer Caliper (8) -- 4.5: Addition and Subtraction of Measurements (38) -- 4.6: Multiplication and Division of Measurements (34) -- 4.7: Relative Error and Percent of Error (23) -- 4.8: Color Code of Electrical Resistors (14) -- 4.9: Reading Scales (12) -- 4: Review -- 4: Test -- 4: Cumulative Review -- Chapter 5: Polynomials: An Introduction to Algebra -- 5.1: Fundamental Operations (11) -- 5.2: Simplifying Algebraic Expressions (29) -- 5.3: Addition and Subtraction of Polynomials (19) -- 5.4: Multiplication of Monomials (14) -- 5.5: Multiplication of Polynomials (20) -- 5.6: Division by a Monomial (15) -- 5.7: Division by a Polynomial (12) -- 5: Review -- 5: Test -- Chapter 6: Equations and Formulas -- 6.1: Equations (24) -- 6.2: Equations with Variables in Both Members (10) -- 6.3: Equations with Parentheses (16) -- 6.4: Equations with Fractions (19) -- 6.5: Translating Words into Algebraic Symbols (12) -- 6.6: Applications Involving Equations (14) -- 6.7: Formulas (21) -- 6.8: Substituting Data into Formulas (20) -- 6.9: Reciprocal Formulas Using a Calculator (10) -- 6: Review -- 6: Test -- 6: Cumulative Review -- Chapter 7: Ratio and Proportion -- 7.1: Ratio (35) -- 7.2: Proportion (41) -- 7.3: Direct Variation (14) -- 7.4: Inverse Variation (15) -- 7: Review -- 7: Test -- Chapter 8: Graphing Linear Equations -- 8.1: Linear Equations with Two Variables (19) -- 8.2: Graphing Linear Equations (16) -- 8.3: The Slope of a Line (20) -- 8.4: The Equation of a Line (20) -- 8: Review -- 8: Test -- 8: Cumulative Review -- Chapter 9: Systems of Linear Equations -- 9.1: Solving Pairs of Linear Equations by Graphing (7) -- 9.2: Solving Pairs of Linear Equations by Addition (8) -- 9.3: Solving Pairs of Linear Equations by Substitution (6) -- 9.4: Applications Involving Pairs of Linear Equations (15) -- 9: Review -- 9: Test -- Chapter 10: Factoring Algebraic Expressions -- 10.1: Finding Monomial Factors (10) -- 10.2: Finding the Product of Two Binomials Mentally (13) -- 10.3: Finding Binomial Factors (15) -- 10.4: Special Products (11) -- 10.5: Finding Factors of Special Products (11) -- 10.6: Factoring General Trinomials (9) -- 10: Review -- 10: Test -- 10: Cumulative Review -- Chapter 11: Quadratic Equations -- 11.1: Solving Quadratic Equations by Factoring (17) -- 11.2: The Quadratic Formula (10) -- 11.3: Applications Involving Quadratic Equations (15) -- 11.4: Graphs of Quadratic Equations (10) -- 11.5: Imaginary Numbers (16) -- 11: Review -- 11: Test -- Chapter 12: Geometry -- 12.1: Angles and Polygons (21) -- 12.2: Quadrilaterals (21) -- 12.3: Triangles (28) -- 12.4: Similar Polygons (15) -- 12.5: Circles (25) -- 12.6: Radian Measure (16) -- 12.7: Prisms (14) -- 12.8: Cylinders (19) -- 12.9: Pyramids and Cones (18) -- 12.10: Spheres (11) -- 12: Review -- 12: Test -- 12: Cumulative Review -- Chapter 13: Right Triangle Trigonometry -- 13.1: Trigonometric Ratios (22) -- 13.2: Using Trigonometric Ratios to Find Angles (8) -- 13.3: Using Trigonometric Ratios to Find Sides (8) -- 13.4: Solving Right Triangles (8) -- 13.5: Applications Involving Trigonometric Ratios (23) -- 13: Review -- 13: Test -- Chapter 14: Trigonometry with Any Angle -- 14.1: Sine and Cosine Graphs (15) -- 14.2: Period and Phase Shift (10) -- 14.3: Solving Oblique Triangles: Law of Sines (13) -- 14.4: Law of Sines: The Ambiguous Case (9) -- 14.5: Solving Oblique Triangles: Law of Cosines (19) -- 14: Review -- 14: Test -- 14: Cumulative Review -- Chapter 15: Basic Statistics -- 15.1: Bar Graphs (7) -- 15.2: Circle Graphs (10) -- 15.3: Line Graphs (10) -- 15.4: Other Graphs (10) -- 15.5: Mean Measurement (9) -- 15.6: Other Average Measurements and Percentiles (9) -- 15.7: Range and Standard Deviation (6) -- 15.8: Grouped Data (7) -- 15.9: Standard Deviation for Grouped Data (6) -- 15.10: Statistical Process Control (6) -- 15.11: Other Graphs for Statistical Data (7) -- 15.12: Normal Distribution (8) -- 15.13: Probability (11) -- 15.14: Independent Events (11) -- 15: Review -- 15: Test -- Chapter 16: Binary and Hexadecimal Numbers -- 16.1: Introduction to Binary Numbers (7) -- 16.2: Addition of Binary Numbers (4) -- 16.3: Subtraction of Binary Numbers (5) -- 16.4: Multiplication of Binary Numbers (5) -- 16.5: Conversion from Decimal to Binary System (7) -- 16.6: Conversion from Binary to Decimal System (5) -- 16.7: Introduction to the Hexadecimal System (7) -- 16.8: Conversion from Decimal to Hexadecimal System (6) -- 16.9: Conversion from Hexadecimal to Decimal System (5) -- 16.10: Conversion from Binary to Hexadecimal System (4) -- 16: Review -- 16: Test -- Appendix A: Powers and Roots -- Appendix B: Calculator Math -- Index
Includes index.
Keywords: Mathematics -- Textbooks